„Jelenia strzałem zwalam z nóg…” O znaczeniu polowań w „Scenach myśliwskich z Dolnej Bawarii" Martina Sperra - Feliszewski, Zbigniew (Zoophilologica. Polish Journal of Animal Studies, 2018)
The article is an attempt to read the early play of a German play wright Martin Sperr, from the perspective of hunting theory. In the play Hunting scenes from Bavaria of 1966, Martin Sperr shows the mechanisms of exclusion of a human being from the society. The play is set in a Bavarian vil- lage – a community on the threshold of economic, political and cultural changes, transforming from a production society into a consumer society. The economic crisis exaggerates the processes of exclusion, which culminates in the literal hunting for homosexual Abram. The article is an attempt to analyse the hunting artefact as a way to show the individual processes of exclusion from the community.